Comorbidities and outcomes in South Asian individuals with chronic kidney disease: an observational primary care cohort. Issue 1 (13th January 2021) - Major, Rupert W; Shepherd, David; Medcalf, James F; Xu, Gang; Gray, Laura J; Brunskill, Nigel J
Abstract: Background: South Asian (SA) individuals are more likely to develop end-stage renal disease (ESRD), but how chronic kidney disease (CKD) differs in relation to demographics, comorbidities and outcomes has not been studied. We aimed to study differences in SA individuals with CKD compared with White individuals. Methods: This was an observational CKD cohort comparing SA with White individuals. Inclusion criteria were ≥18 years of age and two or more Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) eGFRs <60 mL/min/1.73 m 2 >3 months apart. Individuals with ESRD at baseline were excluded. Baseline characteristics, including eGFR formulae [CKD-EPI and CKD-EPI-Pakistan (CKD-EPI-PK)], were compared. Analysis using competing risk regression for cardiovascular (CV) and ESRD events and Cox proportional hazard model for mortality was performed. Results: From an adult population of 277 248 individuals, 17 248 individuals had CKD, of whom 1990 (11.5%) were of SA ethnicity. Age-adjusted prevalence of CKD was similar between ethnicities. SA individuals were more likely to be male, younger and socioeconomically deprived, and to have diabetes mellitus, CV disease and advanced CKD. Mean CKD-EPI-PK eGFR was 6.5 mL/min/1.73 m 2 lower (41.1 versus 47.6, 95% confidence interval for difference 6.47–6.56) than for CKD-EPI. During 5 years of follow-up, 5109 (29.6%) individuals died, 2072 (12.0%) had a CV and 156 (0.90%) an ESRD event. Risk for SA individuals was higher for ESRD, similar to CV events and lower for mortality. Each 1 mL/min/1.73 m 2 decrease in CKD-EPI-PK was associated with a 13.1% increased ESRD risk (adjusted subdistribution hazard ratio 0.869, 95% confidence interval 0.841–0.898). Conclusions: SA individuals with CKD were younger and had more advanced disease than White individuals. Risk of ESRD was higher and CKD-EPI-PK was associated with ESRD risk in SA individuals. Specific CKD interventions, including the use of CKD-EPI-PK, should be considered in SA populations.